In silico evaluation of brazilin (Caesalpinia sappan L.) as a Dpre1 Mycobacterium tuberculosis inhibitor - Entuy Kurniawan; Sulaeman Sulaeman; Dwi Krihariyani; Evi Diah Woelansari (Poltekkes Kemenkes Bandung, 2026)
Background: The increasing incidence of drug-resistant Mycobacterium tuberculosis (Mtb) necessitates the identification of novel molecular targets and therapeutic candidates. Decaprenylphosphoryl-β-D-ribose 2′-epimerase subunit 1 (DprE1) is a key enzyme in Mtb cell wall biosynthesis and represents a promising therapeutic target. Brazilin, a natural compound derived from Caesalpinia sappan L., has been reported to exhibit diverse biological activities; however, its interaction with DprE1 remains insufficiently explored, highlighting a gap for computational-based investigation. Objective: To evaluate the binding affinity and molecular interaction profile of brazilin against DprE1 through an in silico approach. Methods: Molecular docking was performed using the crystal structure of DprE1 (PDB ID: 5OEP) with Molegro Virtual Docker. Key parameters included an active-site grid radius of 15 Å, grid resolution of 0.30 Å, and 10 independent docking runs per ligand to ensure reproducibility. Method validation was performed via redocking of the native ligand, yielding an RMSD <2.0 Å. Binding affinity and interaction patterns of brazilin were compared with rifampicin, isoniazid, and the native ligand. Results: Brazilin exhibited a rerank score of −71.287, indicating moderate binding affinity, stronger than isoniazid but lower than rifampicin and the native ligand. Notably, brazilin consistently occupied the catalytic binding pocket and established hydrogen bonding and hydrophobic interactions with key residues, suggesting a stable and functionally relevant binding orientation. This represents the first target-specific computational evidence linking brazilin to DprE1 inhibition. Conclusion: Brazilin from Caesalpinia sappan L. shows potential as a natural DprE1 of Mycobacterium tuberculosis inhibitor, although further experimental validation is required to confirm its biological efficacy.